Boost radiotherapy in young women with ductal carcinoma in situ: a multicentre, retrospective study of the Rare Cancer Network - (:unkn) unknown (LANCET LTD, 2006)
Background Outcome data in young women with ductal carcinoma in situ (DCIS) are rare. The benefits of boost radiotherapy in this group are also unknown. We aimed to assess the effect of boost radiotherapy in young patients with DCIS. Methods We included 373 women from 18 institutions who met the following inclusion criteria: having tumour status Tis and nodal status (N)0, age 45 years or younger at diagnosis, and having had breast-conserving surgery. 57 (15%) patients had no radiotherapy after surgery, 166 (45%) had radiotherapy without boost (median dose 50 Gy [range 40-60]), and 150 (40%) had radiotherapy with boost (60 Gy [53-76]). The primary outcome was local relapse-free survival. Findings Median follow-up was 72 months (range 1-281). 55 (15%) patients had local relapse. Local relapse-free survival at 10 years was 46% (95% Cl 24-67) for patients given no radiotherapy, 72% (61-83) for those given radiotherapy without boost, and 86% (78-93) for those given radiotherapy and boost (difference between all three groups, p<0.0001). Age, margin status, and radiotherapy dose were significant predictors of local relapse-free survival. Compared with patients who had no radiotherapy, those who had radiotherapy had a decreased risk of local relapse (without boost, hazard ratio 0.33 [95% CI 0.16-0.71], p=0.004; with boost, 0.15 [0.06-0.36], p<0.0001). Interpretation In the absence of randomised trials, boost radiotherapy should be considered in addition to surgery for breast-conserving treatment for DCIS.
Keywords: BREAST-CONSERVING THERAPY; RANDOMIZED CONTROLLED-TRIAL; SURGICAL ADJUVANT BREAST; LOCAL RECURRENCE; AGE; TAMOXIFEN; RADIATION; FEATURES; STANDARD; IMPACT